PERANCANGAN APLIKASI PENGGAJIAN KARYAWAN PADA SMP ISLAM TAMAN QURANIYAH BERBASIS JAVA - Fitriyani Fitriyani; Dwi Yulistyanti; Nurul Laeli (Universitas Singaperbangsa Karawang, 2020)
Taman Quraniyah Islamic Junior High School is an educational institution founded by a foundation that is growing rapidly in order to create a younger generation who is smarter and more responsible. Taman Quraniyah Islamic Junior High School is located at Jalan Melati No. 100 RT 003/004 Tanjung Barat, Jagakarsa, South Jakarta. The research objective is to design an employee payroll system that can manage data and information accurately, provide a quality service system that is computerized so that the payroll transaction process can be carried out quickly and easily and the making of reports on data can be done more effectively because previously data collection was carried out. manually so that the information obtained by the school is considered inaccurate. The application software used by researchers is Java NetBeans and for database processing using MYSQL.